Microbiome multi-omics analysis reveals novel biomarkers and mechanisms linked with CD etiopathology - Gerard Serrano-Gómez; Francisca Yañez; Zaida Soler; Marc Pons-Tarin; Luis Mayorga; Claudia Herrera-deGuise; Natalia Borruel; Antonio Rodriguez-Sinovas; Marta Consegal; Isaac Manjón; Sara Vega-Abellaneda; Chaysavanh Manichanh (Biomarker Research)
Abstract Background The gut microbiome plays a key role in the development of inflammatory bowel disease (IBD), as imbalances in microbial composition are associated with immune dysfunction. However, the specific mechanisms by which certain microorganisms contribute to this process remain unclear. Methods Here, we employed a multi-omics approach on fecal samples to identify novel microbiome markers and elucidate mechanisms underlying IBD. Shotgun metagenomics was applied to 212 samples (850 in total with validation cohort), shotgun metatranscriptomics to 103 samples and metabolomics to 105 samples. Machine learning techniques were used to predict disease and the three omics data were integrated to propose a mechanistic role of the microbiota. Results Metagenomic analysis identified Crohn's disease (CD)-specific microbiome signatures, including a panel of 20 species that achieved a high diagnostic performance, with an area under the ROC curve (AUC) of 0.94 in an external validation set. Metatranscriptomic analysis revealed significant alterations in microbial fermentation pathways in CD, but not in ulcerative colitis (UC), highlighting disruptions that explain the depletion of butyrate—a key anti-inflammatory metabolite—observed in metabolomics analysis. Integrative multi-omics analyses further identified active virulence factor genes in CD, predominantly originating from the adherent-invasive Escherichia coli (AIEC). Notably, these findings unveiled novel mechanisms, including E. coli-mediated aspartate depletion and the utilization of propionate, which drives the expression of the ompA virulence gene, critical for bacterial adherence and invasion of the host’s macrophages. Interestingly, these microbiome alterations were absent in UC, underscoring distinct mechanisms of disease development between the two IBD subtypes. Conclusions In conclusion, our study not only identifies promising novel biomarkers with strong diagnostic potential, which could be valuable in challenging clinical scenarios, but also offers an integrated multi-omics perspective on the microbial mechanisms underlying inflammation and virulence in Crohn's disease.